ANALYSIS OF OIL CHARACTERISTICS FROM PYROLYSIS OF LOW DENSITY POLYETHYLENE (LDPE) PLASTIC WASTE IN A SMALL CAPACITY REACTOR - Purnama, Ari; Effendy, Marwan; Ngafwan, Ngafwan (International Journal of Mechanical Engineering Technologies and Applications, 2024)
Plastic waste in Indonesia remains a significant unresolved issue, particularly due to the extensive use of plastic bags in the food sector, industry, and other areas, which adversely affects the environment. Addressing this, one effective approach is converting plastic waste into fuel oil through the pyrolysis process. The process involves preparing pyrolysis equipment and extracting oil by conducting laboratory tests on the properties of pyrolysis oil, including Gas Chromatography-Mass Spectrometry (GCMS), Fourier Transform Infrared (FTIR) spectroscopy, and droplet combustion tests. Pyrolysis is performed by heating plastic waste at temperatures ranging from 250°C to 400°C. This study focuses on pyrolysis oil derived from Low-Density Polyethylene (LDPE) plastic, which can be used as an alternative fuel. The results show that pyrolysis oil can be ignited with sparks at a heating temperature of 300°C, exhibiting a viscosity of 1.1378 cP and a calorific value of 10,965.2 cal/g.